A Meta-review Analysis of Research on Technology-assisted Content and Language Integrated Learning (International Conference on Computers in Education, 2020)
Currently, the integration of Content and Language Integrated Learning (CLIL) and digital technology has become widespread all around the world mostly in European countries, which is used for teaching English as a foreign language. However, the trend of using digital technology integrated CLIL in English language education still lacks systematic analysis. The present study aims to examine the published research articles in academic journals, indexed by the Scopus database from 2010 to 2019 was conducted to investigate in terms of nationalities, authors, journals, research methods, research issues, technology learning materials, and educational stages. The finding revealed that the use of CLIL integrated digital technology in English language learning has been positively successful in developing students’ learning motivation and competence, not only technological skills but also content subjects and English language competencies. The results show that video technology was the most popular tool for enhancing students’ motivation and promoting students’ learning ability in English language within the context of CLIL methodology. Therefore, the highest interesting research method was system development that concern of digital technology development which contributes to better effective learning tools. Based on the overall finding, it is clear that CLIL integrated digital technology is an effective tool in English foreign language learning. Although the studies quite still rather low in the last recent year and also mainly in European countries that focusing on higher educational participants, it could bring some challenges of the limited practice to explore the use of CLIL blended technology in learning English in school within Asian countries that are increasingly bilingual setting.